Enhancing Cocoa Bean Drying Efficiency Using an Indirect Solar Dryer with Silica Gel Integration - Muhammad Wildan Alkhair; Bahri Widodo, Syamsul; Abdullah, Nazaruddin; Syntia, Rita (Fakultas Teknik Universitas Samudra, 2025)
Indonesia is one of the world's largest cocoa producers; however, traditional cocoa bean drying methods pose significant challenges, including weather dependency and contamination risks. This study aims to enhance the drying efficiency and product quality by employing an indirect solar dryer integrated with silica gel as a humidity reducer. Experimental research was conducted in the open field area of the Faculty of Engineering, Universitas Samudra, Langsa. The results demonstrate that the use of silica gel effectively stabilizes air temperature and accelerates moisture reduction compared to drying without silica gel. The developed solar drying system reduced the moisture content of cocoa beans by up to 38% within 4 hours, producing a more hygienic final product than manual drying, which achieved only a 21% reduction. This solar dryer technology offers a promising alternative solution for cocoa farmers to improve productivity and product quality sustainably.